สถานการณ์ทางสังคมและจิตลักษณะที่เกี่ยวข้องกับพฤติกรรมใฝ่รู้ใฝ่เรียนดนตรีของนักเรียนวิชาเอกดนตรีระดับชั้นมัธยมศึกษาตอนปลาย - บำเพ็ญทาน(Theeraphong Bampenthan) ธีรพงศ์; พึ่งโพธิ์สภ(Narisara Peungposop) นริสรา (Journal of Behavioral Science for Development, 2016)
(SOCIOLOGICAL SITUATIONS AND PSYCHOLOGICAL CHARACTERISTICS RELATED TO CURIOUS IN MUSIC LEARNING BEHAVIORS OF HIGH SCHOOL STUDENTS) Abstract The purpose of this study aims to study the predictive power on curious in music learning behaviors of high school students on socio characteristic and psychological characteristic in overall group and biosocial factors group. The samples are consisted of 457 students who are high school students with music major at College of Music Mahidol University, Matthayom Sangkeet Wittaya Bangkok School, Wat Suthi Wararam School and Srinakharinwirot University Demonstration School (Secondary) which were selected by multistage random sampling. The research consisted of 10 instruments which were in the form of summated rating scale. The reliability with alpha coefficients was between .76 - .93. The data was analized by Stepwise Multiple Regression Analysis. The research findings were the important variables to predicted the curious in music learning behavior were musical information acceptation, goal setting for music study, achievement motive and relationship between music teachers and students which could predict the curious in music learning behavior at 57%. For the curious in music learning behavior in classroom, the important variables were positive attitude to the curious in music learning behavior, achievement motive, goal setting for music study, internal locus of control, relationship between music teachers and students, parent’s music learning support, and the awareness of others expectations which could predicted curious in music learning behavior in classroom at 42.8%. For the curious in music learning behavior outside classroom, the important predictors were goal setting for music study, achievement motive, musical information acceptation, the others expectations awareness and internal locus of control which could predicted curious in music learning behavior outside classroom at 42.7%. Keywords: Music Learning , Curious in music learning